(untitled) (Journal of Philosophy Culture and Political Science, 2016)
The article discusses the history of the spread of Islam in Western Europe, current status, importance and value characteristics of the process. The problem of Islam in Europe is one of the most important issues of our time. The history of the penetration of Islam in Europe was of multidirectional and multidimensional. Islamic culture since its spread has given a lot of positive results. This is reflected in the literature and studies on the issue. On the achievements of Muslim scholars, and much has been said by the Western researchers. The interaction of culture and civilization was made possible also thanks to the penetration of Islam in the West. Thanks to the achievements of Islamic civilization made possible a more intensive interaction of East and West.